Discussion about developing securitisation in Poland with participation of securitisation investment funds - Buszko, Michał; Krupa, Dorota (Ekonomia i Prawo. Economics and Law, 2016)
Motivation: The paper refers to the issue of development of securitisation in Poland. Securitisation is a multipurpose financial technique commonly used in many countries, especially in those with highly developed capital markets. Such technique supports assets and liabilities management, transfers risks as well as leads to creation innovative, assets-based securities. As Polish financial institutions, especially banks, are facing new challenges related to regulatory capital, long-term financing, non-performing debts and taxation, we examine if securitisation may be developed and successfully used on Polish financial market. In the paper, we discuss the development securitisation in Poland, focusing on legal, financial and structural aspects. Aim: the aim of the paper is to evaluate the conditions of using and developing securitisation in Poland with regard to performing as well as non-performing assets. We also evaluate the role and significance of securitisation investment funds, i.e. special type of investment funds operating in Poland, which are evaluated as the most suitable SPVs for securitisation. Results: upon the research, we conclude that in Poland the most dynamically developing segment of securitisation is that based on non-performing debts, and its significance will be growing altogether with the growth and consolidation of Polish debt collection market. We also conclude that the major barrier related to development of this area of finance is a lack of precise legal and tax regulations.